Efficient difunctional alkaline electrolysis water electrode and preparation method thereof
By continuously electrodeposition on the nickel mesh substrate, the NiFeW alloy layer is solved, and the problems of complexity and cost of catalysts in existing electrolytic equipment are realized, and a high-efficiency, stable and low-cost dual-functional alkaline electrolytic water electrode is achieved, which is suitable for industrial applications.
Patent Information
- Application Number
- CN202411801667.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-07
AI Technical Summary
Existing electrolytic water-lysis equipment requires two different types of catalysts, which leads to increased equipment complexity and operating costs. The existing dual-function electrolytic water-lysis catalysts are costly and complex in preparation processes, making it difficult to expand to industrial applications.
Using a nickel mesh as the substrate, through a two-step continuous electrodeposition method, a Ni deposition layer was first deposited, and then a NiFeW alloy layer was deposited to form an efficient bifunctional alkaline electrolytic water electrode. This method is simple and easy to control, low cost, and can quickly deposition at room temperature.
It achieves low hydrogen evolution overpotential and low oxygen evolution overpotential, has good electrode stability and fast reaction kinetics, and can effectively expand in actual industrial applications, reducing different synthesis processes of electrocatalysts, simplifying the water electrolysis device, and reducing costs.
Smart Images

Figure CN119571384A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogen production by water electrolysis, and in particular to a high-efficiency dual-functional alkaline water electrolysis electrode and a preparation method thereof. Background Art
[0002] In the process of progress and development of human civilization, energy resources are indispensable. The development and utilization of energy have always attracted people's attention. With the rapid development of modern society, the demand for energy is also increasing. The increasing depletion of non-renewable resources and the increasing degree of environmental pollution caused by fossil fuels have made energy and environmental issues particularly prominent. Therefore, there is an urgent need to develop new sustainable energy with broad prospects and environmental friendliness. Hydrogen energy is safe and clean, and its production and effective storage are the key to the development of hydrogen economy. Hydrogen production by water electrolysis, that is, water produces hydrogen and oxygen under the action of electrical energy. This process is green and sustainable, can produce a large amount of hydrogen in a short time, is highly efficient and pollution-free, and is one of the most promising methods so far. As we all know, the reaction processes of HER and OER involve multi-step electron transfer, ion adsorption and diffusion, adsorption of adsorbents, mass transfer processes, kinetic high reaction barriers, etc., all of which require high catalytic and low-cost electrocatalysts to achieve the hydrogen production process. It is known that platinum in HER and platinum-based groups and ruthenium oxide and iridium oxide in OER are the best noble metal catalysts, but they are limited by factors such as high prices and scarce earth reserves, which limits their large-scale application. Therefore, the search for non-noble metal catalysts that are abundant in storage, economical and can replace precious metals has received more and more attention. Due to the advantages of abundant reserves and low cost of first transition metal materials, they have received widespread attention. The development and utilization of abundant transition metal compounds as catalysts for electrocatalytic water decomposition has become a research hotspot today.
[0003] Most of the current catalysts usually have high catalytic activity for only one reaction (OER or HER), so the electrolysis of water requires two different types of catalysts. This makes the electrolysis of water equipment more complicated and increases the operating cost. In addition, the reported bifunctional electrolysis catalysts suitable for alkaline environments, such as NiFe ternary LDH doped with V, Co, etc., are difficult to expand into actual industrial applications due to their high cost and complex preparation process (high temperature, high pressure or long synthesis time), so the efficiency of large-scale water splitting applications is low. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a high-efficiency bifunctional alkaline water electrolysis electrode and a preparation method thereof, which has low hydrogen evolution overpotential and low oxygen evolution overpotential and good stability, and can be deposited in a short time at room temperature. The method is simple, easy to control, low-cost, and can be expanded to actual industrial applications.
[0005] In order to solve the above technical problems, the present invention provides a high-efficiency bifunctional alkaline water electrolysis electrode, comprising a nickel mesh, a Ni deposition layer is deposited on the surface of the nickel mesh, and a NiFeW alloy layer is deposited on the surface of the Ni deposition layer.
[0006] A method for preparing a water electrolysis electrode comprises the following steps:
[0007] Step 1) pre-treating the nickel mesh substrate;
[0008] Step 2) dissolving nickel salt, conductive salt and additive in water to obtain a nickel electrodeposition solution;
[0009] Dissolving nickel salt, iron salt, tungsten salt and additives in water to obtain a nickel-iron-tungsten electrodeposition solution;
[0010] Step 3) placing the pretreated nickel mesh substrate in a nickel electrodeposition solution for constant current deposition to obtain a first electrode of a Ni deposition layer supported on the nickel mesh substrate;
[0011] Step 4) placing the first electrode in a nickel-iron-tungsten electrodeposition solution for constant current deposition to obtain a NiFeW alloy layer supported on the Ni deposition layer, thereby obtaining a finished electrode.
[0012] Furthermore, in step 1), the surface is firstly sandblasted to increase the surface roughness of the nickel mesh, and then degreasing and surface oxide layer treatment is performed. The treatment process includes acid treatment, water washing, and vacuum drying of the nickel mesh in sequence. The acid used for the acid treatment is one of hydrochloric acid or sulfuric acid, and the concentration is 5-25%.
[0013] Furthermore, in step 2), the nickel salt in the nickel electrodeposition solution is nickel chloride and / or nickel sulfate, the conductive salt is one of sodium chloride and sodium sulfate, the additive is boric acid, the nickel salt concentration is 0.1mol / L-1mol / L, the conductive salt concentration is 0.5mol / L-3mol / L, and the additive concentration is 0.01mol / L-0.2mol / L.
[0014] Further, in step 2), the nickel salt in the nickel-iron-tungsten electrodeposition solution is nickel chloride and / or nickel sulfate, the iron salt is ferrous chloride and / or ferrous sulfate, the tungsten salt is sodium tungstate, the additive is boric acid and / or trisodium citrate, the nickel salt concentration is 0.01mol / L-0.1mol / L, the iron salt concentration is 0.005mol / L-0.05mol / L, the tungsten salt concentration is 0.002mol / L-0.01mol / L, and the additive concentration is 0.1mol / L-1mol / L.
[0015] Furthermore, the pH value of the nickel electrodeposition solution and / or the nickel-iron-tungsten electrodeposition solution is in the range of 4-6, and the pH regulator is boric acid, citric acid, hydrochloric acid or sodium hydroxide.
[0016] Further, in step 3), deposition is performed by a three-electrode system, wherein the three-electrode system includes a working electrode, a counter electrode and a reference electrode, the working electrode is a pretreated nickel mesh substrate, the counter electrode is a nickel plate, the reference electrode is a saturated calomel electrode, and the current density of the electrodeposition is -5 mA / cm 2 To -50mA / cm 2 , the deposition time is 10min-60min.
[0017] Further, in step 4), deposition is performed by a three-electrode system, wherein the three-electrode system includes a working electrode, a counter electrode and a reference electrode, the working electrode is a deposition layer electrode, the counter electrode is a nickel plate, and the reference electrode is a saturated calomel electrode, and the current density of the electrodeposition is -10 mA / cm 2 To -80mA / cm 2 , the deposition time is 10min-60min.
[0018] Furthermore, in step 4), after the NiFeW alloy layer is deposited, it is rinsed with deionized water and placed in a vacuum drying oven for drying to obtain a finished electrode.
[0019] Beneficial effects of the present invention:
[0020] 1. A continuous two-step electrodeposition method is used. First, a Ni deposition layer is deposited on the nickel mesh substrate. The Ni deposition layer and the nickel mesh substrate are of the same material. The two are tightly combined. Ni can effectively adsorb the generated hydrogen intermediates and reorganize them into hydrogen molecules. Secondly, a NiFeW alloy layer is deposited. W shows the best adsorption energy for hydrogen intermediates (*H), which can promote the combination of *H and form H in HER. 2 In addition, high-valent tungsten exhibits a strong electron-capture affinity, which can reduce the kinetic barrier in OER.
[0021] 2. As a transition layer, the Ni deposition layer can enhance the adhesion between the NiFeW alloy layer and the substrate. The Ni deposition layer is not only tightly bonded to the nickel mesh substrate, but also tightly bonded to the NiFeW alloy layer. The Ni deposition layer provides a larger specific surface area for the NiFeW alloy layer, increases its nucleation points, and makes the nucleation uniform, so that it has better bonding with the Ni deposition layer and improves the electrode stability.
[0022] 2. During the water electrolysis process, the strong interaction between the two deposited layers will lead to electron transfer at the interface, which can improve the electrolysis efficiency.
[0023] 3. Ni-NiFeW has faster reaction kinetics than single-phase NiFeW or Ni, and can exhibit excellent overall water splitting performance as both cathode and anode
[0024] 4. The Ni-NiFeW bifunctional water electrolysis electrode can avoid the different synthesis processes of electrocatalysts, simplify the water electrolysis device to reduce costs. In addition, it is prepared by electrodeposition, which is simple to operate, easy to control the process, does not require the synthesis of complex surface morphology, and is easy to commercialize and expand production. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is a SEM image of Comparative Example 2 of the present invention;
[0026] Figure 2 is a SEM image of Example 2 of the present invention;
[0027] Figure 3 : is the LSV diagram of hydrogen evolution of the comparative example and the embodiment of the present invention;
[0028] Figure 4 : is the oxygen evolution LSV diagram of the comparative example and the embodiment of the present invention;
[0029] Figure 5 is the electrochemical impedance spectra of the comparative example and the embodiment of the present invention;
[0030] Figure 6 is a current density-voltage relationship curve diagram of a comparative example and an embodiment of the present invention;
[0031] Figure 7 It is a graph showing the relationship between the operating time and voltage of the comparative example and the embodiment of the present invention. DETAILED DESCRIPTION
[0032] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0033] An embodiment of the high-efficiency bifunctional alkaline water electrolysis electrode of the present invention comprises a nickel mesh substrate, a Ni deposition layer is deposited on the surface of the nickel mesh substrate, and a NiFeW alloy layer is deposited on the surface of the Ni deposition layer. The Ni deposition layer is not only tightly bonded to the nickel mesh substrate, but also closely connected to the NiFeW alloy layer. The Ni deposition layer provides a larger specific surface area for the NiFeW alloy layer, and increases its nucleation points and uniform nucleation, so that it has better bonding with the Ni deposition layer, and improves the stability of the electrode.
[0034] Specifically, the water electrolysis electrode prepared in the present application is described in detail with the following multiple comparative examples and embodiments.
[0035] Comparative Example 1:
[0036] Comparative Example 1 is a pretreated commercial 46-mesh nickel mesh, which is cut into 5cm*5cm pieces and placed in a 20% sulfuric acid solution and heated for 5 hours. After the solution temperature is lowered to room temperature, it is rinsed with clean water until neutral, and then ultrasonicated with deionized water three times, and then placed in a vacuum drying oven and heated at 60°C for 6 hours for use.
[0037] Comparative Example 2:
[0038] Comparative Example 2 is a nickel deposition layer electrodeposited on a commercial 46-mesh nickel screen, comprising the following steps:
[0039] (1) A commercial 46-mesh nickel mesh was cut into 5 cm*5 cm pieces and placed in a 20% sulfuric acid solution and heated at 60°C for 5 h. After the solution temperature was lowered to room temperature, it was rinsed with clean water until neutral, and then sonicated with deionized water three times, each for five minutes.
[0040] (2) 35 mmol of NiSO 4 7H 2 0, 17.5mmol NiCl 2 6H 2 0, 0.35 mol NaCl, 21 mmol H 3 BO 3 Dissolve in 350 mL of deionized water and control the pH of the solution in the range of 5-5.5.
[0041] (3) Electrodeposition was performed in a standard three-electrode system, with the working electrode being the nickel mesh treated in step (1), the counter electrode being a 6 cm*6 cm nickel plate, and the reference electrode being a saturated calomel electrode, which were placed in the solution prepared in step (2) and the solution temperature was maintained at 25°C. Constant current electrodeposition was performed using an Autolab electrochemical workstation with a current density of -10 mA / cm 2 The deposition time was 1000s. After deposition, it was rinsed with deionized water and placed in a vacuum drying oven and heated at 60°C for 12h.
[0042] Comparative Example 3:
[0043] Comparative Example 3 is to electrodeposit nickel-iron-tungsten alloy on a commercial 46-mesh nickel screen, comprising the following steps:
[0044] (1) A commercial 46-mesh nickel mesh was cut into 5 cm*5 cm pieces and placed in a 20% sulfuric acid solution and heated at 60°C for 5 h. After the solution temperature was lowered to room temperature, it was rinsed with clean water until neutral, and then sonicated with deionized water three times, each for five minutes.
[0045] (2) 21 mmol of NiSO 4 7H 2 0,4.2mmolFeSO 4 7H 20,1.4mmol Na 2 WO 4 ·2H 2 0,113mmol H 3 BO 3 Dissolve in 350 mL of deionized water and control the pH of the solution to 5.
[0046] (3) Electrodeposition was performed in a standard three-electrode system, with the working electrode being the nickel mesh treated in step (1), the counter electrode being a 6 cm*6 cm nickel plate, and the reference electrode being a saturated calomel electrode, which were placed in the solution prepared in step (2) and the solution temperature was maintained at 25°C. Constant current electrodeposition was performed using an Autolab electrochemical workstation with a current density of -10 mA / cm 2 The deposition time was 3600s. After deposition, it was rinsed with deionized water and placed in a vacuum drying oven and heated at 60°C for 12h.
[0047] Comparative Example 4:
[0048] Two commercial Raney nickel electrodes were cut into 5cm*5cm, used as cathode and anode respectively, and the diaphragm was a commercial composite diaphragm, which was assembled in an electrolytic cell test device. The electrolyte was 30wt% KOH solution, the temperature was 80℃, and the voltage of the electrolytic cell device was measured at different current densities.
[0049] Embodiment 1:
[0050] (1) A commercial 46-mesh nickel mesh was cut into 5 cm*5 cm pieces and placed in a 20% sulfuric acid solution and heated at 60°C for 5 h. After the solution temperature was lowered to room temperature, it was rinsed with clean water until neutral, and then sonicated with deionized water three times, each for five minutes.
[0051] (2) 35 mmol of NiSO 4 7H 2 0, 17.5mmol NiCl 2 6H 2 0, 0.35 mol NaCl, 21 mmol H 3 BO 3 Dissolve in 350 mL of deionized water and control the pH of the solution to be within the range of 5-5.5.
[0052] (3) Electrodeposition was performed in a standard three-electrode system, with the working electrode being the nickel mesh treated in step (1), the counter electrode being a 6 cm*6 cm nickel plate, and the reference electrode being a saturated calomel electrode, which were placed in the solution prepared in step (2) and the solution temperature was maintained at 25°C. Constant current electrodeposition was performed using an Autolab electrochemical workstation with a current density of -10 mA / cm 2 The deposition time was 1000s and the samples were rinsed with deionized water after deposition.
[0053] (4) 21 mmol of NiSO 4 7H 2 0, 1.75 mmol FeSO 4 7H 2 0,1.4mmol Na 2 WO 4 ·2H 2 0,113.2mmol H 3 BO 3 Dissolve in 350 mL of deionized water and control the pH of the solution to 5.
[0054] (5) Electrodeposition was performed in a standard three-electrode system, with the working electrode being the nickel mesh deposited in step (3), the counter electrode being a 6 cm*6 cm nickel plate, and the reference electrode being a saturated calomel electrode, which were placed in the solution prepared in step (4) and the solution temperature was maintained at 25°C. Constant current electrodeposition was performed using an Autolab electrochemical workstation with a current density of -10 mA / cm 2 The deposition time was 3600s. After deposition, it was rinsed with deionized water and placed in a vacuum drying oven and heated at 60°C for 12h.
[0055] Embodiment 2:
[0056] (1) A commercial 46-mesh nickel mesh was cut into 5 cm*5 cm pieces and placed in a 20% sulfuric acid solution and heated at 60°C for 5 h. After the solution temperature was lowered to room temperature, it was rinsed with clean water until neutral, and then sonicated with deionized water three times, each for five minutes.
[0057] (2) 35 mmol of NiSO 4 7H 2 0, 17.5mmol NiCl 2 6H 2 0, 0.35 mol NaCl, 21 mmol H 3 BO 3 Dissolve in 350 mL of deionized water and control the pH of the solution in the range of 5-5.5.
[0058] (3) Electrodeposition was performed in a standard three-electrode system, with the working electrode being the nickel mesh treated in step (1), the counter electrode being a 6 cm*6 cm nickel plate, and the reference electrode being a saturated calomel electrode, which were placed in the solution prepared in step (2) and the solution temperature was maintained at 25°C. Constant current electrodeposition was performed using an Autolab electrochemical workstation with a current density of -10 mA / cm 2 The deposition time was 1000s and the samples were rinsed with deionized water after deposition.
[0059] (4) 21 mmol of NiSO 4 7H 2 0,4.2mmolFeSO 4 7H 2 0,1.4mmol Na 2 WO 4 ·2H 2 0,113.2mmol H 3 BO 3 Dissolve in 350 mL of deionized water and control the pH of the solution to 5.
[0060] (5) Electrodeposition was performed in a standard three-electrode system, with the working electrode being the nickel mesh deposited in step (3), the counter electrode being a 6 cm*6 cm nickel plate, and the reference electrode being a saturated calomel electrode, which were placed in the solution prepared in step (4) and the solution temperature was maintained at 25°C. Constant current electrodeposition was performed using an Autolab electrochemical workstation with a current density of -10 mA / cm 2 The deposition time was 3600s. After deposition, it was rinsed with deionized water and placed in a vacuum drying oven and heated at 60°C for 12h.
[0061] Embodiment 3:
[0062] (1) A commercial 46-mesh nickel mesh was cut into 5 cm*5 cm pieces and placed in a 20% sulfuric acid solution and heated at 60°C for 5 h. After the solution temperature was lowered to room temperature, it was rinsed with clean water until neutral, and then sonicated with deionized water three times, each for five minutes.
[0063] (2) 35 mmol of NiSO 4 7H 2 0, 17.5mmol NiCl 2 6H 2 0, 0.35 mol NaCl, 21 mmol H 3 BO 3 Dissolve in 350 mL of deionized water and control the pH of the solution in the range of 5-5.5.
[0064] (3) Electrodeposition was performed in a standard three-electrode system, with the working electrode being the nickel mesh treated in step (1), the counter electrode being a 6 cm*6 cm nickel plate, and the reference electrode being a saturated calomel electrode, which were placed in the solution prepared in step (2) and the solution temperature was maintained at 25°C. Constant current electrodeposition was performed using an Autolab electrochemical workstation with a current density of -10 mA / cm 2 The deposition time was 1000s and the samples were rinsed with deionized water after deposition.
[0065] (4) 21 mmol of NiSO 4 7H2 0, 10.5 mmol FeSO 4 7H 2 0,1.4mmol Na 2 WO 4 ·2H 2 0,113.2mmol H 3 BO 3 Dissolve in 350 mL of deionized water and control the pH of the solution to 5.
[0066] (5) Electrodeposition was performed in a standard three-electrode system, with the working electrode being the nickel mesh deposited in step (3), the counter electrode being a 6 cm*6 cm nickel plate, and the reference electrode being a saturated calomel electrode, which were placed in the solution prepared in step (4) and the solution temperature was maintained at 25°C. Constant current electrodeposition was performed using an Autolab electrochemical workstation with a current density of -10 mA / cm 2 The deposition time was 3600s. After deposition, it was rinsed with deionized water and placed in a vacuum drying oven and heated at 60°C for 12h.
[0067] Embodiment 4:
[0068] (1) A commercial 46-mesh nickel mesh was cut into 5 cm*5 cm pieces and placed in a 20% sulfuric acid solution and heated at 60°C for 5 h. After the solution temperature was lowered to room temperature, it was rinsed with clean water until neutral, and then sonicated with deionized water three times, each for five minutes.
[0069] (2) 35 mmol of NiSO 4 7H 2 0, 17.5mmol NiCl 2 6H 2 0, 0.35 mol NaCl, 21 mmol H 3 BO 3 Dissolve in 350 mL of deionized water and control the pH of the solution in the range of 5-5.5.
[0070] (3) Electrodeposition was performed in a standard three-electrode system, with the working electrode being the nickel mesh treated in step (1), the counter electrode being a 6 cm*6 cm nickel plate, and the reference electrode being a saturated calomel electrode, which were placed in the solution prepared in step (2) and the solution temperature was maintained at 25°C. Constant current electrodeposition was performed using an Autolab electrochemical workstation with a current density of -10 mA / cm 2 The deposition time was 1000s and the samples were rinsed with deionized water after deposition.
[0071] (4) 21 mmol of NiSO 4 7H 2 0,4.2mmolFeSO 47H 2 0,2.8mmolNa 2 WO 4 ·2H 2 0,113.2mmol H 3 BO 3 Dissolve in 350 mL of deionized water and control the pH of the solution to 5.
[0072] (5) Electrodeposition was performed in a standard three-electrode system, with the working electrode being the nickel mesh deposited in step (3), the counter electrode being a 6 cm*6 cm nickel plate, and the reference electrode being a saturated calomel electrode, which were placed in the solution prepared in step (4) and the solution temperature was maintained at 25°C. Constant current electrodeposition was performed using an Autolab electrochemical workstation with a current density of -10 mA / cm 2 The deposition time was 3600s. After deposition, it was rinsed with deionized water and placed in a vacuum drying oven and heated at 60°C for 12h.
[0073] Regarding electrode morphology analysis, Figure 1 and Figure 2 The SEM images of the deposited single-phase Ni electrode and the Ni-NiFeW composite electrode prepared in Comparative Example 2 and Example 2 are shown in FIG. Figure 1 It can be seen that the surface of the deposited single-phase Ni is a spindle-shaped structure with sharp ends and a wide middle, which has a large specific surface area. Figure 2 It can be seen that the electrode surface is a large round package with many small bulges and small grains on the round package, which can provide more active centers for the electrode. Table 1 shows the atomic percentages of Ni, Fe, and W in the Ni-NiFeW composite electrodes prepared in Examples 1-4. From Table 1, it can be seen that the atomic percentage of Ni in the composite electrodes prepared in Examples 1-4 ranges from 35% to 90%, the atomic percentage of Fe ranges from 9% to 62%, and the atomic percentage of W ranges from 0.2% to 1.3%.
[0074] Regarding the alkaline hydrogen and oxygen evolution performance test and EIS test, HER and OER performance tests were carried out in a standard three-electrode system. The working electrode was the electrode prepared in Comparative Examples 1-3 and Examples 1-4, the counter electrode was a graphite rod, and the reference electrode was a Hg / HgO electrode, which was placed in a 1 mol / L electrolyte at room temperature (25°C). The linear sweep voltammetry (LSV) test was performed using an Autolab electrochemical workstation. The voltage range of the HER performance test was 0V to -0.67V (vs RHE), and the voltage range of the OER performance test was 1.83V to 0.927V (vs RHE). The overpotential was not IR compensated, and the frequency range of the EIS test was 10 -1 ~10 -5 From Table 2, Figure 3 and Figure 4It can be seen that the composite electrodes of Examples 1-4 have a current density of 10 mA / cm 2 The hydrogen evolution overpotential and oxygen evolution overpotential are lower than those of the pretreated nickel mesh (Comparative Example 1) and the NiFeW electrode deposited only (Comparative Example 3). The electrode of Example 2 in Examples 1-4 has a current density of 10 mA / cm 2 The hydrogen evolution overpotential is the lowest, the oxygen evolution overpotential is also low, and the hydrogen evolution performance is similar to that of the Ni deposited layer electrode (Comparative Example 2), indicating that the Ni-NiFeW composite electrode is a relatively excellent bifunctional alkaline water electrolysis electrode. The charge transfer resistance describes the transfer of electrons from the electrocatalyst surface to the reactants in the electrolyte, which is related to the kinetics of the sample. Lower charge transfer resistance indicates faster reaction kinetics, such as Figure 4 From the semicircle of the high frequency range of the EIS spectrum, it can be seen that the charge transfer resistance of Examples 1-4 is smaller than that of Comparative Examples 2 and 3, indicating that the Ni-NiFeW composite electrode has faster reaction kinetics than single-phase Ni or NiFeW.
[0075] Regarding the electrolytic cell test and stability test, two 5cm*5cm Ni-NiFeW composite electrodes were used as cathode and anode respectively, and the diaphragm was a commercial composite diaphragm. They were assembled in the electrolytic cell test device, the electrolyte was 30wt% KOH solution, the temperature was 80℃, and the voltage of the electrolytic cell device was measured at different current densities. Figure 6 As shown, the voltage of Examples 1-4 is lower than that of commercial Raney nickel at the same current density. 2 At the current density of 10000A / m, the voltages of the assembled electrolytic cells of Examples 1-4 were 1.649V, 1.645V, 1.663V, and 1.687V, respectively, which were 50mV, 54mV, 36mV, and 12mV lower than the voltage of the electrolytic cell assembled by commercial Raney nickel in Comparative Example 4 (1.699V). 2 Under the current density, the voltage of the assembled electrolytic cell of Examples 1-4 was 1.849V, 1.836V, 1.854V, and 1.878V, respectively, which was 63mV, 76mV, 58mV, and 34mV lower than the voltage of the electrolytic cell assembled by commercial Raney nickel in Comparative Example 4 (1.912V). Two 5cm*5cm composite electrodes were used as cathode and anode respectively, and the diaphragm was a commercial composite diaphragm. They were assembled in an electrolytic cell test device, the electrolyte was 30wt% KOH solution, the temperature was 80℃, and the current was 1000A / m 2 Run at the current density for 100 h and record the voltage of the electrolytic cell device, such as Figure 7As shown, the voltages of Examples 1-4 increased by 22 mV, 27 mV, 37 mV, and 41 mV, respectively, after 100 h, which are lower than the voltage of Comparative Example 3 (increased by 76 mV), and have good stability, indicating that the Ni-NiFeW composite electrode has excellent practical application performance.
[0076] Table 1
[0077]
[0078] Table 2
[0079] <![CDATA[Hydrogen evolution overpotential (10 mA / cm 2 )]]> <![CDATA[Oxygen evolution overpotential (10 mA / cm 2 )]]> Comparative Example 1 183mV 384mV Comparative Example 2 70mV 351mV Comparative Example 3 150mV 289mV Example 1 88mV 247mV Example 2 81mV 236mV Example 3 109mV 228mV Example 4 95mV 255mV
[0080] The above embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Any equivalent substitution or change made by a person skilled in the art based on the present invention is within the protection scope of the present invention.
Claims
1. A high-efficiency dual-functional alkaline water electrolysis electrode, characterized in that: It comprises a nickel mesh, a Ni deposition layer is deposited on the surface of the nickel mesh, and a NiFeW alloy layer is deposited on the surface of the Ni deposition layer.
2. A method for preparing a water electrolysis electrode, characterized in that: The following steps are involved: Step 1) pre-treating the nickel mesh substrate; Step 2) dissolving nickel salt, conductive salt and additive in water to obtain a nickel electrodeposition solution; Dissolving nickel salt, iron salt, tungsten salt and additives in water to obtain a nickel-iron-tungsten electrodeposition solution; Step 3) placing the pretreated nickel mesh substrate in a nickel electrodeposition solution for constant current deposition to obtain a first electrode of a Ni deposition layer supported on the nickel mesh substrate; Step 4) placing the first electrode in a nickel-iron-tungsten electrodeposition solution for constant current deposition to obtain a NiFeW alloy layer supported on the Ni deposition layer, thereby obtaining a finished electrode.
3. The method for preparing the water electrolysis electrode according to claim 1, characterized in that: In step 1), the surface is firstly sandblasted to increase the surface roughness of the nickel mesh, and then degreasing and surface oxide layer treatment is performed. The treatment process includes acid treatment, water washing, and vacuum drying of the nickel mesh in sequence. The acid used for the acid treatment is one of hydrochloric acid or sulfuric acid, and the concentration is 5-25%.
4. The method for preparing a water electrolysis electrode according to claim 1, wherein: In step 2), the nickel salt in the nickel electrodeposition solution is nickel chloride and / or nickel sulfate, the conductive salt is one of sodium chloride and sodium sulfate, the additive is boric acid, the nickel salt concentration is 0.1mol / L-1mol / L, the conductive salt concentration is 0.5mol / L-3mol / L, and the additive concentration is 0.01mol / L-0.2mol / L.
5. The method for preparing the water electrolysis electrode according to claim 1, characterized in that: In step 2), the nickel salt in the nickel-iron-tungsten electrodeposition solution is nickel chloride and / or nickel sulfate, the iron salt is ferrous chloride and / or ferrous sulfate, the tungsten salt is sodium tungstate, the additive is boric acid and / or trisodium citrate, the nickel salt concentration is 0.01mol / L-0.1mol / L, the iron salt concentration is 0.005mol / L-0.05mol / L, the tungsten salt concentration is 0.002mol / L-0.01mol / L, and the additive concentration is 0.1mol / L-1mol / L.
6. The method for preparing a water electrolysis electrode according to claim 1, wherein: The pH value of the nickel electrodeposition solution and / or the nickel-iron-tungsten electrodeposition solution is in the range of 4-6, and the pH regulator is boric acid, citric acid, hydrochloric acid or sodium hydroxide.
7. The method for preparing a water electrolysis electrode according to claim 1, wherein: In step 3), deposition is performed by a three-electrode system, wherein the three-electrode system includes a working electrode, a counter electrode and a reference electrode, wherein the working electrode is a pretreated nickel mesh substrate, the counter electrode is a nickel plate, and the reference electrode is a saturated calomel electrode. The current density of the electrodeposition is -5 mA / cm 2 To -50mA / cm 2 , the deposition time is 10min-60min.
8. The method for preparing a water electrolysis electrode according to claim 1, wherein: In step 4), deposition is performed by a three-electrode system, wherein the three-electrode system includes a working electrode, a counter electrode and a reference electrode, wherein the working electrode is a deposition layer electrode, the counter electrode is a nickel plate, and the reference electrode is a saturated calomel electrode. The current density of the electrodeposition is -10 mA / cm 2 To -80mA / cm 2 , the deposition time is 10min-60min.
9. The method for preparing a water electrolysis electrode according to claim 1, wherein: In step 4), after the NiFeW alloy layer is deposited, it is rinsed with deionized water and placed in a vacuum drying oven for drying to obtain a finished electrode.
Citation Information
Cited By
Preparation method and application of industrial-oriented alkaline hydrogen production difunctional electrode
CN121228313A
Preparation method of alkaline hydrogen production bifunctional electrode for industrialization and application thereof
CN121228313B
Multi-component alloy hydrogen evolution electrode and preparation method and application thereof
CN121321035A